Hubungan Riwayat Penyakit Infeksi Dengan Kejadian Stunting Pada Balita Umur 24-59 Bulan Di Wilayah Kerja Puskesmas Marawola Kabupaten Sigi: History of Infectious Diseases with Stunting Incidence among Toddlers Age 24-59 Months at the Marawola Health Center, Sigi Regency - Arie Maineny; Olkamien Jesdika Longulo; Nur Endang (Jurnal Bidan Cerdas, 2022)
Introduction: Stunting is a lack of nutrients due to insufficient nutrient accumulation. In 2019, the prevalence of stunting in Sigi Regency was 18.0%, with 3,542 cases (24.6%). Marawola Public Health Center is one of 19 Puskesmas in Sigi Regency, with a stunting prevalence of 28.05% in 2019 and 28.22% in 2020. Objectives: The purpose of this study was to determine whether there is a relationship between a history of infectious disease and the incidence of stunting in children aged 24-59 months in the operational area of ​​the Marawola Health Center, Sigi Regency. Methods: Case-control design with analytical survey method and retrospective approach. The population in this study were all children under five from the Marawola Health Center, Sigi Regency, with an age range of 24 to 59 months. This research technique uses purposive sampling by taking a sample of 41 cases and 41 controls. This research includes univariate and biavariate analysis, as well as chi square test. Results: Statistical tests showed a p-value of 0.000 and an OR of 0.111 between a history of infectious diarrheal disease and the incidence of stunting, as well as a p-value of 0.023 and an OR of 5.484 between a history of ARI infection and the incidence of stunting. Conclusion: The incidence of stunting in children aged 24-59 months is associated with a history of infectious diarrheal diseases and ARI infections. Implementation of the program in the form of stunting prevention education, prevention of infectious diarrheal diseases, and prevention of ARI.   ABSTRAK Pendahuluan: Stunting adalah kekurangan zat gizi akibat akumulasi gizi yang tidak mencukupi. Pada tahun 2019, prevalensi stunting di Kabupaten Sigi sebesar 18,0 %, dengan 3.542 kasus (24,6 %). Puskesmas Marawola merupakan salah satu dari 19 Puskesmas Kabupaten Sigi, dengan prevalensi stunting sebesar 28,05 % pada tahun 2019 dan 28,22 % pada tahun 2020. Tujuan: Tujuan penelitian ini adalah untuk melihat adakah hubungan riwayat penyakit menular dengan kejadian stunting pada anak usia 24-59 bulan di wilayah operasional Puskesmas Marawola Kabupaten Sigi. Metode: Desain kasus kontrol dengan metode survei analitik dan pendekatan retrospektif. Populasi dalam penelitian ini semua balita dari Puskesmas Marawola Kabupaten Sigi, dengan rentang usia 24 sampai 59 bulan. Teknik Penelitian ini menggunakan purposive sampling dengan mengambil sampel 41 kasus dan 41 kontrol. Penelitian ini meliputi analisis univariat dan biavariat, serta uji chi square. Hasil: Uji statistik menunjukkan hubungan p-value 0,000 dan OR 0,111 antara riwayat penyakit diare menular dengan kejadian stunting, serta hubungan p-value 0,023 dan OR 5,484 antara riwayat infeksi ISPA dengan kejadian stunting. Kesimpulan: Kejadian stunting pada anak usia 24-59 bulan berhubungan dengan riwayat penyakit diare menular dan infeksi ISPA. Implementasi program berupa edukasi pencegahan stunting, pencegahan penyakit diare menular, dan pencegahan ISPA.